2009
DOI: 10.1007/s12282-009-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic directional vacuum-assisted breast biopsy using lateral approach

Abstract: With the lateral approach, it is possible to use 11G probes if the breast is thin (in our study minimum thickness was 10 mm) with only polyethylene foam. We believe this to be an advantage of the lateral approach. This advantage is very important in stereotactic biopsy, especially in Japan, as Japanese women's breasts are generally thinner than most Western women's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…1A), and the lateral approach involves inserting the needle parallel to the compression paddle (Fig. 1B) (5, 7). In our study, the mean breast thickness for which stereotactic biopsy with a vertical approach could be performed was 4.0 ± 1.2 cm, whereas the lateral approach could be performed in breasts with a mean thickness of 2.7 ± 1.0 cm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1A), and the lateral approach involves inserting the needle parallel to the compression paddle (Fig. 1B) (5, 7). In our study, the mean breast thickness for which stereotactic biopsy with a vertical approach could be performed was 4.0 ± 1.2 cm, whereas the lateral approach could be performed in breasts with a mean thickness of 2.7 ± 1.0 cm.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was statistically significant ( p < 0.0001); thus, we found that the lateral approach could be performed on thinner breast tissues. Recent studies have also reported that the lateral approach could be performed on thinner breasts than the vertical approach (5, 7, 17). In one such study, the minimal breast thickness for which the lateral approach could be performed was 1 cm (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vasovagal episodes and patient discomfort have been reported. 11 Additionally, there can be logistical difficulties with NL because coordination between surgeon and radiologist is necessary for optimal outcomes.…”
Section: Discussionmentioning
confidence: 99%